Vimentin: from a cytoskeletal protein to a critical modulator of immune response and a target for infection - Arrindell, Jeffrey; Desnues, Benoit (Frontiers in Immunology, 2023)
Vimentin is an intermediate filament protein that plays a role in cell processes, including cell migration, cell shape and plasticity, or organelle anchorage. However, studies from over the last quarter-century revealed that vimentin can be expressed at the cell surface and even secreted and that its implications in cell physiology largely exceed structural and cytoskeletal functions. Consequently, vimentin contributes to several pathophysiological conditions such as cancer, autoimmune and inflammatory diseases, or infection. In this review, we aimed at covering these various roles and highlighting vimentin implications in the immune response. We also provide an overview on how some microbes including bacteria and viruses have acquired the ability to circumvent vimentin functions in order to interfere with host responses and promote their uptake, persistence and egress from host cells. Lastly, we discuss the therapeutic approaches associated with vimentin targeting, leading to several beneficial effects such as preventing infection, limiting inflammatory responses or the progression of cancerous events.